AN ANALYSIS OF THE BARRIERS TO LEARNING QUR’ANIC READING AMONG RURAL MOTHERS: A Case Study of Wih Ilang Village, Takengon - Hatta, Muhammad; Chasani, Muchamad Toif; Mahara, Rijal (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background The ability of mothers to read the Qur’an still encounters various challenges in practice. This study aims to identify the causal factors experienced by mothers in learning Qur’anic recitation. Purpose: The mapping process was carried out through the recognition and categorization of the different forms of obstacles faced by rural mothers in their efforts to learn Qur’anic reading. Method: This research employs a qualitative method, specifically a case study with a grounded research approach. The study began with selecting cases from the population in rural Takengon. Three cases were chosen based on the consideration that this phenomenon reflects the reality currently taking place in the village. These three cases were then carefully observed. Result: The study found that the difficulties and obstacles faced by mothers in reading the Qur’an are caused by various factors involving important elements determining the success of Qur’anic reading. At least five main causes of difficulties and obstacles were identified, first cognitive limitations related to knowledge of Qur’anic sciences, second limited religious knowledge among most mothers, resulting in a weak foundation for correctly understanding Qur’anic recitation, third time constraints due to domestic duties and household responsibilities, which prevent consistent participation in learning, fourth a limited number of Qur’an teachers in the village, causing inadequate guidance for all participants, fifth the village’s difficult geographical conditions worsen accessibility to regular learning activities. Conclusion: Furthermore, the author categorizes the problems in learning Qur’anic reading into three aspects: cognitive and religious barriers, structural and resource barriers, and geographical and accessibility barriers. The findings indicate that these three types of obstacles are closely interrelated and require a holistic and sustainable approach to coaching and development.